A TESE DO MARCO TEMPORAL E A VIOLAÇÃO DOS DIREITOS DOS POVOS ORIGINÁRIOS - MEIRA, Francieli de Oliveira; CABROCHA, Alaíde Guerreiro; PIAZER, Tâmy de Souza; ROCHA, Hohana Valery Marques; KHALAF, Camila Cristina de Souza (ANAIS DO ENIC, 2024)
-